Tools for strengthening peer review in the Journal of the Faculty of Medicine, another step to increase its impact and visibility (2017)
The Journal of the Faculty of Medicine (Revista de la Facultad de Medicina) of the Universidad Nacional de Colombia, after being in the A2 category for ten years, was classified in the B category during the Call 768 of 2016 for Indexing Specialized Colombian Scientific Journals - Publindex (1), which is valid until September 15, 2019.This new categorization occurred despite the notable evolution of the Journal in the past months, which aimed at increasing the visibility and impact of the published scientific production. To achieve this increase, the Journal migrated its editorial process to the Open Journal System (OJS) and implemented the progressive publication of articles in English starting with the coming issues (2). This is also consistent with its purpose: "to disseminate knowledge on various scientific, social and artistic fields related to health sciences, their professional practice and teaching processes.”